Self-Preservation and Self-Governance of the Youth: A Literary Darwinian Perspective of Ever After High Series by Shannon Hale - Donny, Indhira Zikri; Rizano, Gindho; Yeni, Marliza (Politeknik Negeri Padang, 2024)
This article discusses the Ever After High fantasy series by Shannon Hale using literary Darwinism. The theories used are adaptationist literary studies by Joseph Carroll and learned mechanism theory by Davis M. Buss. The two theories above analyze how characters in the novel navigate restrictive traditions, preserve their lives and prestige, and contend with generational demands and conditioning imposed by their elders. This research analyzes three books in the series, using library research, by focusing on a) characters’ motives of preserving their lives, building reputations, and creating a new idea, and a) conflicts that characters’ experience in relation to traditional values and ideas. Throughout the three novels, Hale presents several relations regarding the character’s motives and self-preservation. First, each character, actively engages in self-preservation, whether or not this means adhering to societal standards or tradition. Second, those who reject tradition do so because the tradition itself is a danger to their happiness and their survival. Third, those who accept or partake in traditional custom, do so because the tradition or the status quo gives them certain privileges or advantages. The characters in the series also all engage in self-governance. Despite the differences in the way they view tradition, the author presents the youngster characters in a way that reaffirms their unique personal identity. Ultimately, the books show a Darwinian truth about younger generations. Whether they reject the tradition and upbringing that have been pushed onto them, or whether they accept tradition and are participating in regeneration of tradition, both demonstrate the importance of self-governance and survival.